Exploring the mechanisms under Zuogui Pill’s treatment of ischemic stroke through network pharmacology and in vitro experimental verification - Li, Li; Liu, Yan; Zheng, Yawei; Zhu, Jian; Wu, Dan; Yan, Xiaohui; Li, Changyin; Wu, Minghua; Li, Wenlei (Frontiers in Pharmacology, 2023)
Due to its high mortality, incidence and disability rates, ischemic stroke poses heavy economic burdens to families and society. Zuogui Pill (ZGP) is a classic Chinese medicine for tonifying the kidney, which is effective for the recovery of neurological function after ischemic stroke. However, Zuogui Pill has not been evaluated for its potential effects on ischemic strokes. Using network pharmacology, the research aimed to explore the mechanisms of Zuogui Pill on ischemic stroke, which were further validated in SH-SY5Y cells injured by oxygen and glucose deprivation/reperfusion (OGD/R). Network analysis of Zuogui Pill identified 86 active ingredients and 107 compound-related targets correlated with ischemic stroke. Additionally, 11 core active compounds were obtained, such as Quercetin, beta sitosterol, and stigmasterol. Most of the compounds have been proven to have pharmacological activities. Based on pathway enrichment studies, Zuogui Pill may exert neuroprotection through MAPK signaling, PI3K-Akt signaling and apoptosis, as well as enhance neurite outgrowth and axonal regeneration effect via mTOR signaling, p53 signaling and Wnt signaling pathways. In vitro experiment, the viability of ischemic neuron treated with Zuogui Pill was increased, and the ability of neurite outgrowth was significantly improved. Western blot assays shown that the pro-neurite outgrowth effect of Zuogui Pill on ischemic stroke may be relate to PTEN/mTOR signal pathway. The results of the study provided new insights into Zuogui Pill’s molecular mechanism in treatment of ischemic stroke, as well as clinical references for its use.